Die ‘Godvraagstuk’ enkele flitse - Coetzee, P. J. (Koers, 1980)
Op 9 November 1965 het ’n “doodberig” in ’n Amerikaanse tydskrif te Atlanta, Georgia, verskyn. Onder andere word gemeld: “God, creator of the universe, principal deity of the world’s Jews, ultimate reality of Chris tians, and most eminent of all divinities, died late yesterday during major surgery undertaken to correct a massive diminishing influence. Reaction from the world’s great and from the man in the street was uniformly in credulous ..... From Independence former president Harry S. Truman re- cieved the news in his Kansas City barbershop, and said, ‘I’m always sorry to hear somebody is dead. It’s a damn shame’